Mating preferences and consequences of choosing sibling or non-sibling mates by females of the predator Podisus nigrispinus (Heteroptera: Pentatomidae) - Poderoso, Júlio César Melo; Zanuncio, José Cola; Puker, Anderson; Ramalho, Francisco de Souza; Wilcken, Carlos Frederico [UNESP]; Lima, Eraldo (De Gruyter, 2013)
The sex with the greater investment in offspring is more careful in selecting sexual partners. Mating preferences and consequences of choosing sibling or non- sibling males by Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) females were investigated. Females of this predator were placed with sibling, non- sibling or both types of males in 500 mL plastic containers. The numbers of matings and egg masses per female were registered after 12 h. Eggs were transferred to Petri dishes (9.5 x 1.5 cm) and the number of nymphs that hatched were recorded daily until 10 days after each oviposition. Female longevity with sibling, non-sibling or both types of males was registered and adults were weighed and measured after their deaths. Females of P. nigrispinus did not discriminate between sibling or non- sibling males, which can lead to inbreeding. However, the greater number of eggs laid and the higher egg viability of P. nigrispinus females that mated with non- sibling males indicate that this predator can avoid inbreeding depression including reduced fitness by mating with unrelated males.
Keywords: Biological control; Choice mate; Sexual selection; Stinkbug